2004
DOI: 10.1093/ajcn/80.5.1159
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols and endurance training combine to favorably alter plasma lipid profiles in previously sedentary hypercholesterolemic adults after 8 wk

Abstract: In comparison with plant sterols or exercise alone, the combination of plant sterols and exercise yields the most beneficial alterations in lipid profiles. Implementation of such a combination therapy could improve lipid profiles in those at risk of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
(31 reference statements)
1
32
0
Order By: Relevance
“…With the advent of functional foods and nutraceuticals, an increasing number of patients with moderately elevated blood lipids, or clinical hyperlipidemia, are now searching for natural products or diet interventions, as alternatives to the use of cholesterol-lowering drugs, to optimize their blood lipid levels. Phytosterols and their derivatives are the most widely used natural products for lowering blood cholesterol [12,[20][21][22]. Phytosterols lower plasma cholesterol by inhibiting intestinal cholesterol absorption [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of functional foods and nutraceuticals, an increasing number of patients with moderately elevated blood lipids, or clinical hyperlipidemia, are now searching for natural products or diet interventions, as alternatives to the use of cholesterol-lowering drugs, to optimize their blood lipid levels. Phytosterols and their derivatives are the most widely used natural products for lowering blood cholesterol [12,[20][21][22]. Phytosterols lower plasma cholesterol by inhibiting intestinal cholesterol absorption [12,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols lower plasma cholesterol by inhibiting intestinal cholesterol absorption [12,[23][24][25]. However, the cholesterol-lowering efficacy of phytosterols is low compared to cholesterol drugs [15,16].In addition, phytosterols have no effect on plasma TAG levels [12,[20][21][22]. Therefore, it is important to develop novel natural products or formulations that possess higher cholesterollowering efficiencies and are also able to reduce plasma TAG as well.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of sterols has now been unquestionably established through many earlier (Weststrate and Meijer, 1998) and recent studies (Hallikainen et al, 2000;Vanstone et al, 2002;Varady et al, 2004). It has been shown that plant sterols lower LDL cholesterol concentrations by inhibiting cholesterol absorption in the intestine (Ikeda et al, 1988;Nissinen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, similar studies are available concerning human athletes [7], [22], [23], [24], [25], [26] and [27]. All studies conducted in humans agree on the beneficial effect of aerobic exercise, performed on a regular basis, on lipid profile, and on the positive impact of moderate regular physical activity on the prevention of cardiovascular diseases [23], [24], [25], [26] and [27]. It is important to point out that the lipid transport in horses is not the same as in humans, as a large fraction of lipids, and of cholesterol in particular, is taken up by HDLs [28].…”
Section: Discussionmentioning
confidence: 99%